La atención a los usuarios en el departamento de fiscalización de la prefectura de Los Ríos - Agama Garcia, Talia Liz (2020)
The Provincial Decentralized Autonomous Government of Los Ríos is a legal person under public law that enjoys political, administrative and financial autonomy, and exercises executive, legislative and oversight functions within the territorial district of the province. The problem situation identified is that in many cases the people in charge of user care do not have sufficient training and that customer service is very slow. The general objective is to examine how the care provided to users in this department is. This research is supported under the precepts of the line of investigation of the Administrative Management Model. A field investigation was carried out to collect spontaneous information on the reality that incurs as a problem in the attention to users in the Department of Fiscalization of the Prefecture of Los Ríos and the surveys and interviews that were assigned to the collaborators of the Department of Inspection of the Prefecture of Los Ríos and the users who go to it.